Literature Review Opini Moderasi Beragama - heny triya ningsih (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2023)
Abstract Moderation opinions that are massively rolled out by the government, especially the Ministry of Religion of the Republic of Indonesia, are still interesting to investigate about the deepening of the root facts or causes of the widespread opinion of religious moderation. Looking at the history that can be said to be harmonious between religions even before Indonesia's independence. The purpose of this study is to link the most important cause and synchronize it with the meaning of the word from the cause. Synchronization will also be carried out with public policy theory and civil society involvement in social conflict management. The method used in this study is a literature review research which refers to sources that are considered relevant and from the main sources. The results of the literature review show that there is ambiguity in taking the meaning of radicalism which is considered the main cause of the emergence of moderation opinions, the involvement of civil society by the government to parties who are considered radical or who are considered to carry radical ideas along with experts in their fields, no valid sources are found that explain this. Then joint efforts in handling conflict as part of conflict management must be able to distinguish between violent/radical conflict. These efforts are important to give full rights to the community and minimize new conflicts. Keywords: Moderation, Public Policy, Radicalism